Adherence to treatment in children with Chronic Renal Failure: inclusion of the psychologist to the interdisciplinary team - Guzmán-Carrillo, Karla Yunuén; González-Betanzos, Fabiola; Rivera-Heredia, María Elena; Salazar-Garza, Martha Leticia; Montes-Delgado, Roberto; Aguirre-Martínez, Jorge Iván (Saúde e Sociedade, 2021)
Chronic Kidney Disease (CKD) is one of the main causes of mortality worldwide. In Mexico there are around 140,000 patients with this condition. The aim of this research was understand the factors that facilitate and inhibit the adherence to treatment of pediatric patients with CKD, with interdisciplinary approach and the inclusion of the psychologist to promote comprehensive patient care. A descriptive qualitative study was realized through the interview technique with analysis by categories. Four professionals participated: a doctor, a nurse, a nutritionist and a psychologist of the Children’s Hospital and of Galeno Hemodialysis Clinic in Morelia, Michoacán, Mexico. The results showed the importance of psychological accompaniment to the patient for the acceptance of the diagnosis, emotional management, adherence to treatment and social support, especially with their primary caregiver. Finally, a model of CKD patient care is proposed from an interdisciplinary approach.